5th Anniversary Article: A Lesson from Plants: High‐Speed Soft Robotic Actuators (Adv. Sci. 5/2020). Issue 5 (4th March 2020) - Baumgartner, Richard; Kogler, Alexander; Stadlbauer, Josef M.; Foo, Choon Chiang; Kaltseis, Rainer; Baumgartner, Melanie; Mao, Guoyong; Keplinger, Christoph; Koh, Soo Jin Adrian; Arnold, Nikita; Suo, Zhigang; Kaltenbrunner, Martin; et al.
Abstract : Explosion of ping‐pong balls that is caused by the rapid inflation of an elastomer membrane. The illustrated ultrafast actuation is based on a plant‐inspired mechanical instability that occurs in natural rubber and can be remotely triggered, presented in article number 1903391 by Martin Kaltenbrunner and co‐workers. These new types of high‐speed soft actuators have potential applications in object sorting or grasping.